Generic prot singularities of one-parameter cyclic processes with discount. - Costanza, Vicente (2014)
The subjacent optimal control problem is nontrivial, since the admissible control values are restricted to range over a closed manifold, and so its Hamiltonian may potentially lack regularity. Then, from the mathematical control theory and applied mathematics standpoints it would be worthy to explore the time behavior of the optimal control strategy in individual different situations (economics crisis, cardiac diseases).  In light of the Pontryagin Maximum Principle, the evolution of the optimal costate may also help to clarify further geometric aspects of nonautonomous Hamiltonian dynamical/control systems.